De lo profundo hacia la superficie, construcción del vínculo social en trabajadores del área de salud mental del Hospital Santa Clara. Una mirada desde la psicodinámica laboral. (2018)
The interpersonal relationships that derive in social bonds suggest that individuality itself seeks the alliance with the other, certainly the links drawn between the subjects in the work context, show how important it is for individuals not to isolate themselves and establish contact with them. the others, which indiscriminately will be the source of a number of satisfactions and dissatisfactions typical of the instability in which any relationship of coexistence of the social fabric is formed.